The Influence of Work Environment and Employee Placement on Job Satisfaction and its Impact on Intention to Quit - Zulfikar, Iqbal Valiri; Joeliaty, Joeliaty; Sartika, Dina (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
This study examines the impact of the work environment and employee placement on job satisfaction and how these factors influence the intention to quit among employees in the West Java III Regional Tax Office. Using a quantitative descriptive approach, this research involved a sample of 243 employees directly engaged in tax collection, with data collected via an online questionnaire. The Structural Equation Modeling (SEM) technique was employed for data analysis. The findings reveal that both the work environment and employee placement have a significant positive effect on job satisfaction. A supportive work environment and proper employee placement that aligns with employee skills and qualifications lead to higher job satisfaction and lower intentions to quit. On the contrary, a poor work environment and inappropriate employee placement contribute to increased turnover intentions. Additionally, job satisfaction mediates the relationship between the work environment, employee placement, and the intention to quit. The study highlights the critical role of non-physical work environments, such as organizational culture and employee relations, in influencing job satisfaction. Furthermore, mismatches between employee placement and competencies can aggravate turnover intentions. This research offers valuable insights for the human resource management of government institutions, particularly the Directorate General of Taxes, by suggesting that improving the work environment and ensuring the proper placement of employees can enhance job satisfaction and reduce turnover. The findings suggest practical strategies for managing human resources, ultimately aimed at minimizing employee turnover rates and maintaining organizational effectiveness in tax revenue collection.